Islamism and nationalism among niqabis women in Egypt and Indonesia - Siti Ruhaini Dzuhayatin (Indonesian Journal of Islam and Muslim Societies, 2020)
The phenomenon of the increasing number of niqabis in Indonesia and Egypt has become concern to the government, academics and also civil society. This is due to the involvement of the niqabis or women with the niqab in terrorist networks. The piece of clothing covering the face is not merely a manifestation of faith but it apparently entails a certain ideological doctrine of the so-called Islam kaffah (ultimate Islam) through the establishemnt of Islamic khilafah (Islamic caliphate) as opposed to democracy and modern state. This study aims at observing the extent to which the niqabis negotiate Islam and their nationalism in their respective countries in Indonesia and Egypt where Muslims constitute the majority of the population. This study employed a mix of methods, qualitative and quantitative, involving 205 Niqabis from Indonesia and 87 niqabis from Egypt. The quantitative data were obtained from 292 respondents, while the qualitiative data were collected from 27 niqabis using in-depth interviews through life story technique—6 Egyptians and 21 Indonesians. A number of 12 prominent figures in Egypt and Indonesia were interviewed and two focus group discussions were conducted in both countries involving women activists, academics, government employees, and religious leaders. The framework of this study is the contestation between Islamism and nationalism. This study indicated that there is a significant difference between the niqabis of Indonesia and Egypt in terms of their perception of national pride. Around 30 percent of Indonesian niqabis are not proud of being Indonesian citizens while in Egypt only about 3 percent. Bank interest is used to measure their Islamic refinement through which Niqabis in both countries share a similar view, where almost 90% of them believe that the practice is not Islamic. Moreover, more than 50% support the Caliphate system, which means that one in four niqabis considers that the existing government is thoghut (non Islamic) and nearly 15% agree to defend Islam by means of violence.Fenomena berkembangnya niqabis di Indonesia dan Mesir menjadi perhatian seksama pemerintah, akademisi dan juga masyarakat sipil. Hal ini disebabkan keterlibatan perempuan dalam jaringan teroris yang umumnya menggunakan niqab, sehingga diduga bahwa selembar kain penutup wajah ini tidak semata simbul ketaqwaan tetapi ada bagian dari doktrin ideologi yang melawan sistem yang ada. Pada umumnya, ideologi ini bermaksud mendirikan sistem caliphate yang dilawankan dengan demokrasi dan bentuk negara republik. Penelitian ini bertujuan untuk mengetahui sejauhmana tingkat Islamisme dan nasionalisme para niqabis di Indonesia dan Mesir, sebagai negara dengan mayoritas Muslim. Penelitian ini menggunakan mix-methode, kualitatif dan kuantitatif yang melibatkan 205 Niqabis dari Indonesia dan 87 niqabis dari Mesir. Data kuantitatif diperoleh dari 209 responden melalui kuesioner sedangkan data kualitatif diperoleh melalui wawancara mendalam dengan teknis kisah hidup sebanyak 27, 6 Niqabis Mesir dan 21 Niqabis Indonesia. Disamping itu, dilakukan wawancara dengan 12 tokoh dan dilaksanakan dua diskusi terfokus dengan politisi, aktivis perempuan, akademisi, pegawai pemerintah, dan pemimpin agama. Penelitian ini menggunakan kerangka kerja kontestasi Islamisme dan nasionalisme yang menunjukan hasil sebagai berikut: ada perbedaan signifikan antara niqabis kedua negara pada aspek kebanggaan sebagai warga negara. Hampir 30 persen niqabis Indonesia tidak bangga menjadi WNI sedangkan di Mesir hanya sekitar 3 persen. Jasa Bank digunakan untuk mengukur kehidupan Islami yang menunjukkan kecenderungan sama, meski dengan prosentase yang sedikit berbeda, yaitu lebih dari 90% tidak setuju dengan bunga bank. Terkait dengan politik, lebih dari 50% setuju dengan sistem caliphate dan 1 dari 4 niqabis setuju bahwa pemerintah saat ini thoghut dan sekitar 15 orang setuju menggunakan kekerasan dalam membela negara.